Study on the Increase in the Penetration Power in Accordance With the Changes in the Nozzle Hole of CNG High Pressure Injector - Seok Choe, Mun; se Kim, Kwon; Seuk Choi, Doo (International Journal of Engineering and Technology, 2018)
Background/Objectives: In this research, method of increasing the penetration power of CNG injector, which is the core factor in combustion, was conducted to improve the performances of natural gas vehicle engine.Methods/Statistical analysis: Research was carried out by designing 3D flow line after having assessed each of the compositional factors through 3D modeling. In order to confirm the penetration power according to the shape of the nozzle, models were designed with total hole-number of 4, 8, 12, 16, 20, 24 and 29. The area of nozzle was set within the error rate of 0.05% to minimize the effects of the area.Findings: As an analysis result, during injector spraying, the gas flow was biased toward the outside because the influence of the injector flow is great at injector center. In the case of speed distribution and Mach disk distribution in the after part of the nozzle guide, which is the index of penetration power, it was formed largest in the hole-20 type. Mass flow in injector was verified within the deviation of 0.6% in comparison to the base, irrespective of the number of the holes, while the mass flow was being influenced by injector nozzle area and setting inlet pressure.Improvements/Applications: This analysis was possible to increase the penetration power without affecting the internal shape of the injector and mass flow.Â